SOSIALISASI PENYELENGGARAAN HAJATAN SESUAI PROTOKOL KESEHATAN BAGI APARAT DAN MASYARAKAT DI KELURAHAN TAWANGMANGU KABUPATEN KARANGANYAR - Afni Nooraini; Alvia Callista Makarim (Indonesian Collaboration Journal of Community Services, 2022)
Central Government has implemented the policy of Enforcement of Community Activity Restrictions (PPKM) for Java and Bali regions to suppress the spread of COVID-19. In this policy, Karanganyar Regency Government made Regent Instruction Number: 180/5/2021 which regulates Micro-Based PPKM and the Establishment of the 2019 Corona Virus Disease Handling Post at Village and Sub-District Levels for Corona Virus Disease Control 2019. This policy is a guideline for the community in Karanganyar Regency in organizing celebrations because in its implementation there are still many that do not comply with health protocols, one of which is in Tawangmangu Village. The purpose of this community service activity is to help the Karanganyar Regency Government socialize the Karanganyar Regency Regent's Instructions, especially related to organizing celebrations. The techniques for implementing this community service activity are: 1) Designing infographics about the procedures for carrying out celebrations according to health protocols; 2) Conducting socialization of the organization of celebrations according to health protocols through zoom meetings; 3) Carry out outreach to the community directly about the implementation of the celebration according to the health protocol. The results of this community service activity are increasing public understanding and awareness of the policy of organizing celebrations in accordance with the instructions of the Karanganyar Regency Regent. Recommendations from authors are: (1) Tawangmangu Village Government needs to continue to socialize on an ongoing basis regarding the Regent's Instruction Number 180/5/2021, especially regarding the implementation of celebrations through various media; (2) There is a need to improve two-way communication and coordination with the community so that the community can participate in the above activities; and (3) Tawangmangu Village Government conducts periodic supervision and advises people who violate wisely